The effect of economic value added, profitability, and leverage on stock returns with company value serving as an intervening variable - Suidarma, I Made; Suardana, Ida Bagus Raka; Utomo, Danang Fajar (International Journal of Management and Sustainability, 2025)
This study analyzes the influence of Economic Value Added (EVA), profitability, and leverage on stock returns in the property and real estate sectors, with company value as a mediating variable. Using a quantitative approach with a causal design, the research examined 50 companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023, selected through purposive sampling. Data were sourced from annual reports and financial statements, then analyzed using multiple linear regression. The Sobel test was applied to assess the mediating effect of company value. The findings indicate that EVA, profitability, and leverage significantly affect stock returns. EVA positively influences investor interest by showing the company’s ability to create value. Profitability enhances positive market perception and reflects financial stability. Leverage demonstrates a dual effect: moderate debt usage increases stock returns, while excessive debt raises bankruptcy risk, harming performance. Additionally, company value is found to mediate the relationship between EVA, profitability, leverage, and stock returns. The study suggests that companies in the property and real estate sectors should focus on improving EVA and profitability while managing leverage prudently. By doing so, they can attract investors, enhance stock performance, and support sustainable growth and competitiveness in the capital market.